HUBUNGAN TINGKAT PENGETAHUAN DENGAN MOBILISASI DINI PADA IBU NIFAS DI PUSKESMAS LIKUPANG TIMUR KECAMATAN LIKUPANG TIMUR - Buhari, Ita Sasmita; Hutagaol, Esther; Kundre, Rina (JURNAL KEPERAWATAN, 2015)
Abstract : Early mobilization is a treat to guide mother after giving birth to guide mother going out from her bed and walk as soon as possible. The purpose of this research is to find out the correlation of knowledge level with the early mobilization of mother after giving birth at the East Likupang Primary Health Care Subdistrict East Likupang. The research design is analytical survey with cross sectional approach. This research was conducted in East Likupang Primary Health Care on December 6th – 30th 2014. The sample of this research are total sampling with 50 respondents from November and December who fulfill the criteria of inclusion. The instrument of this research used questionnaire. Statistical test using a computerized system by using the chi-square test (X2) at the level of significance 95% (α = 0.05%). The results obtained by the p-value = 0.000 with the level of significance <0.05. This shows there is a meaningful correlation of knowledge level with the early mobilization of mother after giving birth. The conclusion is, the higher of knowledge level and experience that mother gained, the more easy mother do the early mobilization in a appropriate stages. Keywords : Knowledge Level, Early Mobilization,Mother After Giving Birth Abstrak Latar belakang. Mobilisasi Dini adalah selekas mungkin membimbing ibu keluar dari tempat tidurnya dan membimbing ibu selekas mungkin segera berjalan. Tujuan penelitian untuk mengetahui hubungan tingkat pengetahuan dengan mobilisasi dini pada ibu nifas di puskesmas likupang timur kec. Likupang timur. Desain penelitian Observasional analitik dengan pendekatan cross sectional. Penelitian ini dilakukan di puskesmas Likupang timur pada 6 desember- 30 desember 2014. Sampel dalam penelitian ini adalah total sampling dengan 50 responden dari November dan desember yang memenuhi kriteria inklusi. Instrumen penelitian yaitu menggunakan kuesioner. Uji statistik menggunakan sistem komputerisasi dengan menggunakan uji chi-square () pada tingkat kemaknaan 95% (α = 0,05). Hasil diperoleh hasil p-value = 0,000 dengan level of significance < 0,05. Ini menunjukkan ada hubungan bermakna antara tingkat pengetahuan dengan mobilisasi dini pada ibu nifas. Kesimpulan semakin tinggi tingkat pengetahuan dan pengalaman yang didapat ibu maka semakin akan melakukan mobilisasi dini sesuai tahap-tahap mobilisasi dini. Kata kunci : Tingkat Pengetahuan, Mobilisasi Dini, Ibu Nifas.